Diversity of macaque microbiota compared to the human counterparts. Issue 1 (December 2018) - Chen, Zigui; Yeoh, Yun; Hui, Mamie; Wong, Po; Chan, Martin; Ip, Margaret; Yu, Jun; Burk, Robert; Chan, Francis; Chan, Paul
Abstract Studies on the microbial communities in non-human primate hosts provide unique insights in both evolution and function of microbes related to human health and diseases. Using 16S rRNA gene amplicon profiling, we examined the oral, anal and vaginal microbiota in a group of non-captive rhesus macaques (N = 116) and compared the compositions with the healthy communities from Human Microbiome Project. The macaque microbiota was dominated by Bacteroidetes, Firmicutes and Proteobacteria; however, there were marked differences in phylotypes enriched across body sites indicative of strong niche specialization. Compared to human gut microbiota whereBacteroides predominately enriched, the surveyed macaque anal community exhibited increased abundance ofPrevotella . In contrast to the conserved human vaginal microbiota extremely dominated byLactobacillus, the macaque vaginal microbial composition was highly diverse while lactobacilli were rare. A constant decrease of the vaginal microbiota diversity was observed among macaque samples from juvenile, adult without tubectomy, and adult with tubectomy, with the most notable distinction being the enrichment ofHalomonas in juvenile andSaccharofermentans in contracepted adults. Both macaque and human oral microbiota were colonized with three most common oral bacterial genera:Streptococcus, Haemophilus andVeillonella, and shared relatively conserved communities to each other. A number of bacteria related to human pathogens were consistently detected in macaques. The findings delineate the range of structure and diversity of microbial communities in a wild macaque population, and enable the application of macaque as an animal model for future characterization of microbes in transmission, genomics and function.